Study of cracks in the weld metal joint of p91 steel of a superheater steam pipe. (October 2015) - Tavares, S.S.M.; Pardal, J.M.; Souza, G.C.; Garcia, P.S.P.; Barbosa, E.S.; Barbosa, C.; Cardote Filho, I.
Highlights: ASTM A335 Gr. P91 welded by GMAW metal cored process. Despite of satisfactory results of mechanical test and X-ray had been found, intergranular cracks and pores were observed. Cracks origin is related to residual elements from base metal and weld joint contamination. Chemical composition of base metal should be verified before welding process. An effective clean process should be made before each welding pass. Abstract: Chromium molybdenum alloy steels are employed in high temperature services. Welded components in both fossil–fuel fired and nuclear power plants are some examples of critical applications. This study shows the characterization of the mechanical properties and microstructure of 9Cr–1Mo–V steel, revealing the presence of cracks and pores in the weld metal of a circumferential joint made by GMAW with metal cored wire process. Analyses by Scanning Electron Microscopy (SEM) were performed in samples obtained before and after the post weld heat treatment (PWHT). Supplementary analyses by Energy Dispersive X ray Spectroscopy (EDS) were made at diverse regions where discontinuities occurred. The cracks presented an intergranular propagation. The greater crack was localized in the root neighborhood with approximately 1.8 mm of extension in a sample with post weld heat treatment (PWHT). The fractured surfaces of Charpy specimens were also analysed by EDS–SEM. The results obtained show the cleaning process of the joint and the chemical composition of the wire and base metal can play an important role in the behavior of the weld joint in pipe service; despite the acceptable mechanical tests results, in accordance with the specifications.